2014
DOI: 10.3354/meps10569
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous analysis of δ13C, δ15N and δ34S ratios uncovers food web relationships and the trophic importance of epiphytes in an eelgrass Zostera marina community

Abstract: Simultaneous analysis of carbon, nitrogen and sulphur stable isotope ratios was applied in this pilot study to examine the food web of a Zostera marina L. system in the western Baltic Sea. Samples of 3 potential food sources: eelgrass, epiphytic algae and seston, as well as 69 consumer species were collected during the growing season of Z. marina from March to September 2011. The measured δ 13 C values of epiphytes were close to δ 13 C values of eelgrass, impeding a clear distinction of those 2 carbon sources,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…The majority of stable isotope studies show that food webs in eelgrass meadows are characterized by a large degree of omnivory and fueled mainly through algal and detrital pathways [ 61 , 92 , 93 ]. Correspondingly we found that for both sites phytoplankton contributed most (51–92%) to the sediment organic pool followed by macroalgae (0–45%), whereas the contribution of eelgrass (leaves, rhizomes and roots) was low (<9%).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of stable isotope studies show that food webs in eelgrass meadows are characterized by a large degree of omnivory and fueled mainly through algal and detrital pathways [ 61 , 92 , 93 ]. Correspondingly we found that for both sites phytoplankton contributed most (51–92%) to the sediment organic pool followed by macroalgae (0–45%), whereas the contribution of eelgrass (leaves, rhizomes and roots) was low (<9%).…”
Section: Discussionmentioning
confidence: 99%
“…
Fig. 1 Study area in the Western Baltic Sea and the Kiel Fjord with sampling stations Witlingskuhle ( circle ) and Falkenstein station of Mittermayr et al ( 2014b ) ( plus sign )
…”
Section: Methodsmentioning
confidence: 99%
“…We assume here that this difference is due to trophic fractionation, which would place A. aurita on the upper end of the range reported for other organisms and larger than the value previously reported by D’Ambra et al ( 2014 ). An alternative explanation would be the presence of an additional trophic complexity, e.g., an unidentified dietary source with a higher δ 15 N value and similar δ 34 S value compared to seston not included in our mixing model, although the low δ 34 S values would then still support a more benthic origin of material at the base of the food web in fall (Jaschinski et al 2008 ; Mittermayr et al 2014b ).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Seston, epiphytes and Z. marina were used as ultimate carbon sources for all consumers. Z. marina roots and rhizomes were treated as 1 group of Z. marina below-ground biomass and later excluded for the purpose of this study, as they are not a relevant food source in the studied system (Mittermayr et al 2014). As the carbon of these primary producers travels to the top of the food web, it passes through herbivorous, omnivorous and carnivorous consumers.…”
Section: Stable Isotope Analysismentioning
confidence: 99%